Enhanced Transformation of Atrazine by High Efficient Visible Light-Driven N, S-Codoped TiO2 Nanowires Photocatalysts - Yanlin Zhang (International Journal of Photoenergy, 2014)
Advanced oxidation process using titanium dioxide as a photocatalyst under solar irradiation is one of the most attractive technologies to eliminate atrazine, an endocrine disrupting and carcinogen contaminant. The N, S-codoped TiO2 nanowires at the calcination of 600°C obtained by a facile hydrothermal method revealed the best photocatalytic performance for the degradation of atrazine under visible light irradiation compared to N, S-codoped TiO2 nanoparticles and S-doped TiO2 nanowires. TOC removal experiment also exhibited the similar result and achieved 63% of atrazine mineralization within 6 h. The degradation of atrazine was driven mainly by •OH and holes during the photocatalytic process. Reactive species quantities such •OH and O2•- generated by N, S-codoped TiO2 nanowires under visible light irradiation were much more than those of S-doped TiO2 nanowires and N, S-codoped TiO2 nanoparticles. These results were mainly attributed to the synergistic effect of N and S doping in narrowing the band gap, remarkable increase in electron-hole separation, extending the anatase-to-rutile transformation temperature above 600°C, and preferentially exposing high reactive {001} crystal facets of anatase.